Analisis Pemanfaatan Pembangkit Listrik Tenaga Surya (PLTS) Sebagai Sumber Energi Listrik Pada Base Transceiver Station (BTS) Indosat - Saliban, Pantas; Darma, Amani; -, Rahmaniar (Power Elektronik : Jurnal Orang Elektro, 2024)
The demand for mobile technology services forces communication companies to build numerous Base Transceiver Station (BTS) devices to meet customer needs. The construction of BTS must cover all areas, including remote regions without electricity. One example of a remote island without electricity is Genting Island in Karimunjawa, where the implementation of environmentally friendly renewable energy can serve as a power supply for BTS. One such environmentally friendly power supply is using photovoltaic-based micro-grid systems. Therefore, the availability of 234 kWh of electrical energy with a photovoltaic-based micro-grid system as an ideal power supply for BTS on Genting Island needs to be planned and its economic value analyzed. This micro-grid system data analysis is conducted through simulation on PVSyst. The results of this study indicate that the ideal photovoltaic micro-grid system for BTS uses 192 units of 410 Watt monocrystalline PV modules with 15 units of Solar Charger Controllers, 312 lead-acid batteries, 9 battery inverters, an NVP value of 65,511,705, a PI value of 1.0064, and a DPP value of 25 years.